29 gifts : how a month of giving can change your life - Walker, Cami (Da Capo Lifelong, 2009)
This is the powerful story of the author's struggle with multiple sclerosis and how a healer's unusual prescription of mindful altruism to "give away 29 gifts in 29 days" ignited her energy, her happiness, and invited more abundance into her life.